DIMENSI SUMBER BELAJAR DALAM PRESPEKTIF ISLAM - Purbatua Manurung (Universitas Islam Negeri Sumatera Utara Medan, 2016)
This article was explaining learning resourcess in education according to Association for Education Communication and Technology (AECT) paradigma, has many function of learning resourcess to provide teascher equipments as well as;man or people, massage, matgerials, hardware, procedure or tehnical and setting. Learning resourcess in educational islamic perspektive the constructionon integrated learning sources is getting started religious service with independence tradition/hadits of phropet Muhammad SAW. in our life.Keywords: Dimensi, Sumber Belajar, Perspektif Islam.